Lesion sterilization and tissue repair of primary molar to the eruption of its permanent successor: a case report - Paulo Moreira, Claudia; Maura Coli Siegl, Regina; Kerber Tedesco, Tamara; Gimenez, Thais; Floriano, Isabela; Carlos Imparato, Jose (Brazilian Dental Science, 2022)
The aim of this study is to report a clinical case of lesion sterilization and tissue repair in primary molar, with follow-up until the eruption of the permanent successor. A 6-year-old male patient came to the Pediatric Dentistry Clinic at Faculdade Sao Leopoldo Mandic in Campinas-SP, with his mother, complaining of “caries in several teeth”. On clinical examination, it was found that tooth 85 had a severe carious lesion with pulp involvement and fistula. Radiographically, radiolucency was observed in the furcation region. It was then decided to perform lesion sterilization and tissue repair of the tooth with CTZ paste. After 6 months of the procedure, the tooth was clinically and radiographically normal and after 3 years it was observed that tooth 85 was in complete root resorption. After extraction, the permanent successor erupted naturally without clinical or radiographic alterations. It can be concluded that the present clinical case demonstrated success in the use of CTZ paste in the lesion sterilization and tissue repair of primary molars, until the complete eruption of the permanent successor. KEYWORDS Primary tooth; Pulpectomy; Pediatric dentistry; Endodontics; Case report.